2019
DOI: 10.1088/1742-6596/1240/1/012141
|View full text |Cite
|
Sign up to set email alerts
|

Assesement of Machining Parameters on en-24 Steel Under Dry, Wet and MQL Condition Using Multi Coated Inserts

Abstract: The minimum quantity lubrication is an interesting possibility for an economical and environmentally compatible production, which unifies the functionality of coolants and lubricants with mightily less consumption of lubricants. In this experiment, minimum quantity lubrication setup on turning machine was design and developed for comparison between dry and wet conditions and their effects are considered under different parameters. This setup uses mist/flood formation of lubricants with the help of minimum quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The tool nose radius is highly dominated for developing the cutting forces. Shrajal et al [12] investigate the machining performance on EN −24 steel and it was found that MQL is superior to that of dry and wet conditions for surface roughness. Singh et al [13] focused on the reducing the usage of cutting fluids, an effort has been made to present an overview of the various cutting fluid types, cooling techniques, and important alternatives, such as dry machining, cryogenic cooling, minimal amount lubrication, and hybrid cooling.…”
Section: Introductionmentioning
confidence: 99%
“…The tool nose radius is highly dominated for developing the cutting forces. Shrajal et al [12] investigate the machining performance on EN −24 steel and it was found that MQL is superior to that of dry and wet conditions for surface roughness. Singh et al [13] focused on the reducing the usage of cutting fluids, an effort has been made to present an overview of the various cutting fluid types, cooling techniques, and important alternatives, such as dry machining, cryogenic cooling, minimal amount lubrication, and hybrid cooling.…”
Section: Introductionmentioning
confidence: 99%